THE MENTAL WELLNESS DIFFERENCES BETWEEN SOCIAL SCIENCE AND TECHNOLOGY SCIENCE STUDENTS OF UITM DURING ODL SESSIONS - Hazlin Hasan; Sharifah Norhuda Syed Wahid; Mastura Mohamad; Azwan Shah Aminuddin (Journal of Islamic, Social, Economics and Development, 2022)
The prolonged COVID-19 pandemic has seen an alarming rise of mental health issues amongst university students who were affected academically as well as personally. The study investigated the differences between social science and technology science students of Universiti Teknologi MARA (UiTM) on their depression, anxiety and stress levels during the COVID-19 pandemics as this composition of students proposes an extensive range of mental wellness conditions, yet this composition is often overlooked. 1,617 UiTM students from both social science and technology science fields answered DASS-21 questionnaire online to test their levels of depression, anxiety and stress while attending Open and Distance Learning (ODL) classes. The data was analysed using IBM-SPSS AMOS version 24 software which included the descriptive analysis and an independent t-test which was tested on both fields. The findings suggested that the ODL sessions conducted fully online during the early phase of the pandemic has seen both social science and technology science students were moderately mentally affected with the technology science students showing higher levels of stress, anxiety and depression compared to social science students. The findings also revealed that there existed significance gap on depression and stress scores between both fields (p-values < 0.05), but not on anxiety. The study could be extended in the future to determine the effects of the pandemic on the students’ mental wellness in its later phases, in tandem with the university’s latest mission of achieving Globally Renowned University status which among others focuses on humanity and the wellbeing of its citizen.